Dual-role Women in Selangor: Work-family Conflict and its Impact on Emotional Well- being - Zakaria, Siti Marziah (International Journal of Psychosocial Rehabilitation, 2020)
In this era of urbanization, women have to play roles equal to men especially in making a living to support their families while at the same time, they have to perform their responsibilities as mothers and wives. Subsequently, this situation affects the functioning of families these days. As a result, they are unable to spend enough time with their families due to working overtime or having to take their works home. This article explores work-family conflicts experienced by dual-role women in Selangor and assesses the impacts on their emotional well- being. Eleven (11) informants around Selangor were interviewed thoroughly using semi-structured interview questions. The informants were selected through purposive sampling method. Then, the data were analyzed using the Interpretative Phenomenological Analysis procedure. Results of the analysis showed that work-family conflict among women in the workplace was triggered by career challenges, lack of family time, and unsupportive spouse. The findings of this study can serve as guidelines and references to improve and upgrade the National Women's Policy. The findings of this study should also be noted by the Department of Labor, Human Resources Division, Training Unit, and others in drafting programs and formulating policies for married female employees.